Pressurized hot water extraction of total phenolic, flavonoid and chlorophyll content and browning index from clinacanthus nutan - Noor Faradira Bt Alwi (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Clinacanthus nutans which belongs to the family of Acanthaceae has been used traditionally as herbal remedies in complementary and alternative medicine. The effect of total phenolic (TPC), flavonoid (TFC) and chlorophyll content (TCC) and browning index in the extraction of C. nutans extract using PHWE has been conducted. To extract the phenolic and flavonoid contents, C. nutans were divided into three parts; leaves, stem and mixture of leaves and stem. The parameters that being manipulated are the temperature (120-160 C) and time (10-35 min). Multivariate analysis was used to determine the correlation of total phenolic, flavonoid and chlorophyll content and browning index of C. nutans extracts. Results shows that the mixture of C. nutans extract at temperature 160 C and 25 min contain the highest phenolic and flavonoid content compared to other parts with 1.35 mg GAE/g C. nutans and 2.08 mg QUE/g C. nutans respectively. Chlorophyll content in the extract was found to be very sensitive and rapidly degraded when temperature increase. Chlorophyll content in untreated sample (9.72 mg/l) was significantly decreases to 2.08 mg/l after 10 min of extraction for all samples. Results shows that mixture and leaves of the extract has high browning index compared to stem. Browning of extract occur due to break down of chlorophyll towards temperature. Correlation of TPC, TFC, TCC and browning index was done by using PCA and it was able to discriminate all the samples. Result from PCA shows that mixture and leaves extract contains higher TPC, TFC, TCC and browning index compared to the stem extract